Prospective Randomized Observational Pilot Trial Evaluating the Effect of Information of Early Childhood Intervention on Stress Levels of Parents of Extremely Low Gestational Age Infants at the NICU - Resch, Bernhard; Fröhlich, Judith; Murg, Katharina; Pichler-Stachl, Elisabeth; Hofbauer-Krug, Claudia; Kurz, Ronald (Frontiers in Public Health, 2021)
It is not known to what extent early information on early childhood intervention (ECI) by ECI professionals reduces or increases stress levels of parents having an extremely preterm infant at the neonatal intensive care unit (NICU). Using an observational pilot study, we gave information on ECI in a randomized matter to parents of an extremely low gestational age newborn (ELGAN) at the chronological age of 3–4 weeks (cases) or not (controls). After informed consent, parents judged the infants at the age of 5–7 weeks with the Parental Stressor Scales: Neonatal Intensive Care Unit [PSS: NICU test has three subscales = “Sights and Sounds” (five items), “Parental Role Alteration” (14 items), and “Look and Behave” (seven items)]. Total scales score and subscales scores were comparable between 13 cases and 13 controls over a study period of 1.5 years. Total scores were 9.32 ± 0.72 in the cases compared to 10.02 ± 0.76 in the controls, (95% CI −6.93 to 4.93). Overall, the cases scored lower in most of the items. Early information on ECI at the NICU was provided to parents with an ELGAN did not result in higher stress levels measured with the PSS: NICU. Whether early information on ECI is a strategy, which might be able to reduce parental stress levels, has to be proven in larger studies.